2019
DOI: 10.2134/agronj2018.10.0637
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐Leaf Removal and Nitrogen Application Programs for Flue‐Cured Tobacco Production

Abstract: Core Ideas Lower‐leaf removal will reduce cured leaf yield but can reduce the portion of lower‐demand stalk positionsNitrogen application after leaf removal is of limited value and is currently discouragedIf these programs are to find commercial success, a higher selling price should be offered by leaf purchasers With a current global over‐supply of flue‐cured tobacco (Nicotiana tabacum L.), tobacco producers in North Carolina have been encouraged to remove the lowermost leaves prior to harvest due to their lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…In this study, the proportions of superior middle tobacco and superior tobacco were 91.18–95.83% and 62.19–73.29%, respectively, which is above the theoretical maximum proportion of superior tobacco (60%) 39 . A previous study demonstrated that the removal of four leaves per plant results in a moderate yield of flue-cured tobacco during the tobacco growing season 9 . In this study, the number of left leaves of K326 and the proportion of superior tobacco were higher, whereas the yield and economic value were lower, while the results of the Hongda cultivar were the opposite; this may indicate that the Hongda cultivar is more suited to the Honghe tobacco-planting area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the proportions of superior middle tobacco and superior tobacco were 91.18–95.83% and 62.19–73.29%, respectively, which is above the theoretical maximum proportion of superior tobacco (60%) 39 . A previous study demonstrated that the removal of four leaves per plant results in a moderate yield of flue-cured tobacco during the tobacco growing season 9 . In this study, the number of left leaves of K326 and the proportion of superior tobacco were higher, whereas the yield and economic value were lower, while the results of the Hongda cultivar were the opposite; this may indicate that the Hongda cultivar is more suited to the Honghe tobacco-planting area.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, agronomic practices affect the yield and quality of flue-cured tobacco 5 , 9 , 23 , 44 , 51 . No special agronomic practices have been adopted at the flue-cured tobacco-planting sites sampled in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Row spacing at the Lower Coastal Plain and Oxford Tobacco Research Stations was 44 and 48 in, respectively, and tobacco was transplanted to a density of 6,000 plants/ac. Tobacco was produced using recommendations from the North Carolina Cooperative Extension Service (Fisher, 2016), with the exception of treatments imposed.…”
Section: Location Description and Plot Establishmentmentioning
confidence: 99%
“…Fisher, Vann, Inman, and Brown (2016) and Finch et al. (2019) suggested that the removal of eight leaves might be required to eliminate lug grades of flue‐cured tobacco.…”
Section: Cured Leaf Grade Distributionmentioning
confidence: 99%